Estudio del efecto del radón en los casos de muerte por cáncer pulmonar en la población de Mexicali, Baja California, México - Reyna Carranza, Marco Antonio; López Badilla, Gustavo (Revista Mexicana de Ingenieria Biomedica, 2002)
The concentration level of radon was measured in the interiors of Mexicali city homes, for studying the relationship that the radon could have with the pulmonary cancer death cases in the population. Radon is a radioactive gas and it has a great facility for adhering to the particles that are suspended in the air. When these radioactive particles are inhaled and deposited in the alveolus, little explosions occur and the DNA of the cells is altered, producing cancer in the pulmonary tissues. Urbane, geographical, and meteorological characteristics of Mexicali, are favorable conditions for certain zones of the city to present high concentrations of particles that remain suspended in the atmosphere practically all year long. The radon gas was sampled in the interior air of 95 homes, and the analysis was made by neighborhoods with and without pavement, and by sexes; for establishing if the cancer death cases could be correlated with some of the neighborhood groups and/or with some sex. The study found that the major number of occurred deaths were in the neighborhoods without pavement, and in all cases, female deaths occurred with more frequency and the radon gas concentrations were superior in the homes where a death had occurred, with significative differences from 9.2% to 207% depending on the analyzed group.